Facilitating Cross-Cultural Online Discussion Groups: Issues and Challenges - Sundra Wall Williams; Karen Watkins; Barbara Daley; Bradley Courtenay; Mike Davis; Darryl Dymock (Adult Education Research Conference, 2001)
This action research identifies the issues and challenges experienced by facilitators who moderated cross-cultural group discussion activities in an online environment. This study found that in a cross-cultural online environment, the challenges of the facilitator expand beyond the currently identified range of problems for online discussion.